Estimating marginal causal effects in a secondary analysis of case‐control data. (9th March 2017) - Persson, Emma; Waernbaum, Ingeborg; Lind, Torbjörn
Abstract : When an initial case‐control study is performed, data can be used in a secondary analysis to evaluate the effect of the case‐defining event on later outcomes. In this paper, we study the example in which the role of the event is changed from a response variable to a treatment of interest. If the aim is to estimate marginal effects, such as average effects in the population, the sampling scheme needs to be adjusted for. We study estimators of the average effect of the treatment in a secondary analysis of matched and unmatched case‐control data where the probability of being a case is known. For a general class of estimators, we show the components of the bias resulting from ignoring the sampling scheme and demonstrate a design‐weighted matching estimator of the average causal effect. In simulations, the finite sample properties of the design‐weighted matching estimator are studied. Using a Swedish diabetes incidence register with a matched case‐control design, we study the effect of childhood onset diabetes on the use of antidepressant medication as an adult. Copyright © 2017 John Wiley & Sons, Ltd.